Analisis Perubahan Partai Politik Pemenang Pemilu di Indonesia - Martinus, Handy (Humaniora, 2013)
By three elections in Indonesia, the pattern seen is a change in a very significant political force. It changed not only the party in the first position, but also a different party: three elections produced three different parties that received the most votes. Major political changes in Indonesia have been coloring since the reformation in 1998. The first change occurred in the 1999 election. PDIP evicted Golkar that has ruled for more than 30 years claiming an absolute majority. Then in the 2004 election, the strength of the party with the most votes moved to Golkar. In 2009, a major change occurred again. Top position was taken by Democrats. This article is a study using secondary data from a survey conducted by the Indonesian Survey Institute (LSI) during the period 1 to 12 February 2012 with the population of all Indonesian citizens who have the rights to vote in elections when the survey was conducted. Number of samples taken ranged up to 2,050. Based on the sample, it is estimated margin of error of + / -2.2% at the 95% confidence level. It is concluded that the political change will continue in the 2014 election along with the negative sentiments from Indonesian people against politics and law enforcement today. Election results earlier in some parts of Indonesia showed a progressive trend increasing number of non-voters and swing voters. NasDem and Gerindra are quite prominent in voter mobilization through the air via mass media. Both attract Democrats’ swing voters whom are middle-class which are more intensively following the national news.